ABDULLA AVLONI'S LIFE AND WORK - Suvonova Nilufar (Galaxy International Interdisciplinary Research Journal, 2022)
Abdulla Avloni's views in the field of education are closely connected with the psyche, way of life, national values of the Uzbek people. The rich pedagogical heritage of the writer. and the study of whether it served as a valuable resource is becoming a requirement of the times